A warm-up performed with proper-weight sandbags on the leg improves the speed and RPE performance of 100 m sprint in collegiate male sprinters - Zhai, S. S.; Wen, D. T.; Liu, T. Y.; Hou, W. Q. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Muscle performance can be notably improved following a preloading maximal or near maximal stimulus due to the induction of postactivation potentiation, but the success of a preloading exercise in generating a postactivation potentiation response depends on the balance between fatigue and potentiation. However, the optimal warm-up strategy for sprint runners before a match may be not well established until now. METHODS: Fifteen well-trained male sprint runners performed four different warm-up protocols: warm-up with 0% body mass; warm-up with 2% body mass; warm-up with 4% body mass; warm-up with 8% body mass. The weight-bearing sandbag was tied about 3~5 cm above each ankle joint. During the 100-meter test, the time and rating of perceived exertion (RPE) in the first 30 meters, time in the first 60 meters, and time in the 100 meters were recorded, respectively. Two-high-speed digital video cameras were separately set in the sagittal planes on the left side of a line drawn at a distance of 30 m and 60 m from the start line to record the sprint motion. RESULTS: A warm-up performed with a sandbag weighted 4% of body mass could significantly improve the time and the RPE score of 100 m sprint by improving average velocity, stride frequency, average stride length, and average accelerated velocity during the sections of 0~30 m, 30~60 m and 60~100 m. This positive effect was better than that of 2% body-weigh effect. However, a warm-up performed with a sandbag weighted 8% of body mass had no significant influence on the performance of a 100 m sprint. CONCLUSIONS: Current results indicated that a warm-up performed with proper-weight(4% body mass) sandbags on the leg was beneficial to the improvement of 100 m sprint performance, and the mechanism might be that it effectively activated the main muscles and neuromuscular regulation of running and produced a better postactivation potentiation.